(untitled) (Orfeu, 2026)
This article presents a harmonic, thematic, and formal analysis of Naturale (1985) by Luciano Berio, a work for viola, percussion, and pre-recorded voice that integrates Sicilian folk music with contemporary compositional techniques. Drawing from Voci (1984) and the Corpus di Musiche Popolari Siciliane, Berio constructs a layered musical narrative, combining archival recordings with live performance to explore expressive contrasts and structural cohesion. The analysis reveals how pitch centricity, modular formal design, and thematic transformation shape the work’s dramaturgical arc. Emphasis is placed on the performer’s role in navigating Berio’s intricate interplay between structure and spontaneity, particularly through recurring pitch centers and the integration of folk-derived materials. A section-by-section investigation highlights Berio’s method of structural reuse, harmonic framing, and textural variation, offering insights for both performers and scholars. The study positions Naturale as a hybrid composition that bridges ethnographic authenticity and avant-garde idioms through a multi-dimensional analytical approach.